THE MICROSCOPIC STRUCTURE OF THE VIVIPAROIDEA FOSSIL’S WALL TEXTURE - DATSENKO, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
A detailed examination of the wall textures of the fossil Viviparoidea (Mollusca, Gastropoda, Viviparoidea) has shown that the wall microtexture is verу specific and has some diffenisions for different generas. The elements of the shell structure of Viviparoidea of the different generas has the particular differences, there is also a definite pattern of distribution of some components in the shells of different generas.